Pee-Wee's big adventure [videorecording (Blu-Ray)] - Burton, Tim, 1958-; Shapiro, Robert, 1938-; Abramson, Richard Gilbert; Reubens, Paul, 1952-2023; Hartman, Phil; Daily, E. G.; Holton, Mark, 1958-; Salinger, Diane; Omen, Judd; Elfman, Danny (Warner Bros. Entertainment Inc., 2011)
Pee-wee hits the open road to look for his missing bicycle and encounters riotous adventures with bikers, bums, cowboys, cons, a phantom trucker, and a waitress with wanderlust. Special features included.